Impact of Applying a Learning Strategy to Improve the Sample Quality in Cervical Screening in Nursing Staff in Social Service - Gutiérrez Enríquez, Sandra Olimpia; Méndez Donjuan, Luis Fernando; Terán Figueroa, Yolanda; Gaytán Hernández, Darío; Oros Ovalle, Cuauhtémoc; Díaz Oviedo, Aracely (Investigación y Educación en Enfermería, 2017)
Objective. The study sought to assess the impact of applying a learning strategy to improve the quality of sample collection during cervical screening by students from the Nursing Degree Program doing social service. Methods. This was a longitudinal, quasi-experimental study with the participation of 23 interns from the Nursing Degree Program at a public university from San Luis Potosí, Mexico. The work assessed knowledge of practical skills in taking cervical cytology tests and the quality of samples before and after applying a learning strategy that included 10 h of theoretical training and 22 h of practices on themes related to sample collection in cervical screening. Results. A statistically significant difference was obtained in improved knowledge (t = -12.8 p<0.001) and practical skills (t = -8.86 p<0.001) after the intervention. The increased percentage of suitable samples from 30.43% to 82.60% was attributed to the application of the learning strategy in the pre- and post-intervention phases (p<0.001). Conclusion. Training is effective to improve knowledge and practical skills to collect samples in cervical screening, as well as the quality of the samples for their interpretation. How to cite this article: Gutiérrez SO, Méndez LF, Terán Y, Gaytán D, Oros C, Díaz A. Impact of Applying a Learning Strategy to Improve the Sample Quality in Cervical Screening in Nursing Staff in Social Service. Invest. Educ. Enferm. 2017; 35(3): 340-347.